Segmentation and location computation of bin objects - Hema, Chengalvarayan Radhakrishnamurthy; Paulraj, Murugesapandian; Ramachandran, Nagarajan; Sazali, Yaacob (Ars International, 2009)
http://ezproxy.unimap.edu.my:2081/source/sourceInfo.url?sourceId=144749